Ab Initio energetics of SiO bond cleavage - Huehn, Carolin; Erlebach, Andreas; Mey, Dorothea; Wondraczek, Lothar; Sierka, Marek (Journal of Computational Chemistry, 2017)
A multilevel approach that combines high-level ab initio quantum chemical methods applied to a molecular model of a single, strain-free SiOSi bridge has been used to derive accurate energetics for SiO bond cleavage. The calculated SiO bond dissociation energy and the activation energy for water-assisted SiO bond cleavage of 624 and 163 kJ mol−1, respectively, are in excellent agreement with values derived recently from experimental data. In addition, the activation energy for H2O-assisted SiO bond cleavage is found virtually independent of the amount of water molecules in the vicinity of the reaction site. The estimated reaction energy for this process including zero-point vibrational contribution is in the range of −5 to 19 kJ mol−1. © 2017 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2023-04-20
Keywords: ab initio method; activation energy; CCSD(T); dissociation energy; silica